The Christian Ideal and the Communist Ideology in the Novel by Eugenio Corti “The Red Horse” - Mercantini, Simona; Fedchyshyna, Olena (Accents and Paradoxes of Modern Philology, 2019)
The paper examines the phenomenon of creativity of the Italian writer Eugenio Corti, author of the historical novel Il Cavallo Rosso. Namely, it concerns the specificity of his artistic method and themes. The historical novel Il Cavallo Rosso, describes the 30-year period of Italian history from the pre-war period to the referendum on divorce in post-war Italy in the Seventies, so it points out many different and interesting features. This article will mainly focus the attention on the problems concerning the value of human life and humanity, from the point of view both of the Christian ideal and communist ideology. The novel is especially relevant for modern Ukraine, since it shows how the experience of the war can help rethinking national identity, the significance of history and of human life. Even the war represented for the author the possibility of realizing his own task, i.e. discovering the truth of himself and of the world. He could even say: «War can be an immense advantage. War makes men. The war teaches an infinite number of things because it shows us our fellow men as they are: it teaches us to truly know men». Accepting reality as it is represented to Corti the possibility of realizing its mission to be aware of himself and of man condition in general. The dynamisms of the narration in the novel Il Cavallo Rosso reflect the same dynamisms of life: life never goes on standby, human beings never renounce hope, they keep on looking for new and better answers to their existential questions. In this sense Corti’s novel can be considered historical, not only because the author, fond of history, loved to be extremely faithful to the facts, but also because he admirably managed to make the same mechanisms of history and life. Through his great love for reality and his desire to know it better and let it known to everybody, Corti discovered his vocation in the world of literature: the vocation of being a Witness. And the novel we are talking about is a proof of this, as there are narrated his life experiences and those of his generation. Knowing better Man and History, the Life and its meaning, is the main goal of the big novel Il cavallo rosso, this is why the concepts of “experience”, “testimony” and “anti-testimony” will be highlighted as main components of both the author’s life and his literary vocation.